2002
DOI: 10.4049/jimmunol.169.10.5441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That SHIP-1 Contributes to Phosphatidylinositol 3,4,5-Trisphosphate Metabolism in T Lymphocytes and Can Regulate Novel Phosphoinositide 3-Kinase Effectors

Abstract: The leukemic T cell line Jurkat is deficient in protein expression of the lipid phosphatases Src homology 2 domain containing inositol polyphosphate phosphatase (SHIP) and phosphatase and tensin homolog deleted on chromosome ten (PTEN). We examined whether the lack of expression of SHIP-1 and PTEN is shared by other leukemic T cell lines and PBLs. Analysis of a range of cell lines and PBLs revealed that unlike Jurkat cells, two other well-characterized T cell lines, namely CEM and MOLT-4 cells, expressed the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 49 publications
9
107
0
Order By: Relevance
“…CEM cells contained protein for SHIP-1, but barely detectable levels of SHIP-2, as previously described (Freeburn et al, 2002) (Figure 4). Although SHIP-1 has been described as a negative regulator of immune receptor and cytokine and growth factor receptor signaling (Krystal, 2000), a recent work proposed that SHIP-1 has a positive role in TLR4 signaling, notably by positively regulating NF-kB-dependent gene transcription in response to LPS stimulation (Fang et al, 2004).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…CEM cells contained protein for SHIP-1, but barely detectable levels of SHIP-2, as previously described (Freeburn et al, 2002) (Figure 4). Although SHIP-1 has been described as a negative regulator of immune receptor and cytokine and growth factor receptor signaling (Krystal, 2000), a recent work proposed that SHIP-1 has a positive role in TLR4 signaling, notably by positively regulating NF-kB-dependent gene transcription in response to LPS stimulation (Fang et al, 2004).…”
Section: Resultssupporting
confidence: 83%
“…Differential expression of the lipid phosphatase SHIP-1 in CEM and Jurkat cells Previous works have shown that the Jurkat leukemic cell line is deficient in SHIP-1 at the protein level, but that CEM cells express the protein normally (Bruyns et al, 1999;Freeburn et al, 2002;Horn et al, 2004). To confirm that difference in our cell lines, we carried out Western blotting analysis with specific antibodies raised against SHIP-1 and another inositol lipid phosphatase, namely SHIP-2.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, SHIP is tyrosine-phosphorylated in response to TCR and CD28 ligation (29). Moreover, expression of a constitutively active SHIP mutant in the leukemic T cell line Jurkat regulates constitutive PtdIns(3,4,5)P 3 levels and CD28-activated PI3K effectors (30). In addition, SHIP interacts with Tec kinase and inhibits its function in T cells (31) as well as participates in a negative signaling complex by associating with the adaptor protein LAT (32).…”
Section: Insights Into the Role Of Ship In T Lymphocytes From Gene Tamentioning
confidence: 99%
“…S1). It is noteworthy that the leukemic T-cell line Jurkat is deficient in protein expression of the lipid phosphatases Src homology 2 domain containing inositol polyphosphate phosphatase (SHIP) and the phosphatase and tensin homologue deleted on chromosome 10 (PTEN), which normally counterbalance the PI3K-mediated de novo generation of PIP3 and hence the level of Akt phosphorylation (29). Thus, in the Jurkat cell line, the significant decrease of the Akt phosphorylation observed following edelfosine addition to cell culture could be associated to a direct down-modulation of the PI3K activity or to the abrogation of the PIP3 docking action.…”
Section: Edelfosine Modifies the Membrane Distribution Of Fas And Is mentioning
confidence: 99%